PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN EDUCATION GAMES DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI KELAS IV SDN MAJALENGKA WETAN VII - D. Eriska; Fitri Aprianti; Nurkholis; Sri Rahayu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
P This research has a background of low student learning outcomes in Mathematics. This research aim to applied the Project Based Learning model with the help of Digital Education Games to increase the result in SDN Majalengka Wetan VII. The method used in this research is the Classroom Action Research method. This research consists of two cycles and four stages. In each cycle includes planning, implementation, observation, and reflection. The subject of this research are 14 male students and 18 females students. The observation during the process, using of test in the end of cycle, and documentation during the process used collection data. The results showed that the application of the Project Based Learning learning model with the help of Digital Education Games could improve student learning outcomes in Mathematics class IV-A SDN Majalengka Wetan VII. This is indicated by an increase in the average value and the percentage of learning completeness from pre-cycle to cycle. The average value obtained from pre-cycle is 66.12 with a learning completeness percentage of 34.37%. In cycle I the average value obtained was 77.25 with a learning completeness percentage of 59.38%. In cycle II the average value obtained was 84.97 with a learning completeness percentage of 87.5%. The conclusion is that the application of the Project Based Learning learning model with the help of digital Education Games can improve student learning outcomes in Mathematics in class IV-A SDN Majalengka Wetan VII.